2019
DOI: 10.1067/j.cpradiol.2018.05.007
|View full text |Cite
|
Sign up to set email alerts
|

Health Care Disparities in Radiology: A Primer for Resident Education

Abstract: As the population of the United States grows increasingly diverse, health care disparities become vital to understand and mitigate. The ethical and financial implications of how groups of Americans gain access to health care have evolved into some of today's most challenging socioeconomic problems. Educators in radiology are just beginning to tackle the concepts of health care disparities, unconscious bias, and cultural competency. In July 2017, the Accreditation Council for Graduate Medical Education required… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…Recognizing the role CMR has to play, the Society of Cardiovascular Magnetic Resonance has released guidance, education, and information for the use of CMR in women with CVDs in a drive to address this gender disparity. 71,[74][75][76] How can LF CMR be implemented?…”
Section: Cmr In Hicsmentioning
confidence: 99%
“…Recognizing the role CMR has to play, the Society of Cardiovascular Magnetic Resonance has released guidance, education, and information for the use of CMR in women with CVDs in a drive to address this gender disparity. 71,[74][75][76] How can LF CMR be implemented?…”
Section: Cmr In Hicsmentioning
confidence: 99%
“…population imaging) is influenced by who has access to radiology services in the first place. In many countries, there are significant differences in access to healthcare among social groups [12]. The people who do have the best access to radiology services are most likely the ones most benefitting from the application of the ML technology, because they were represented in the algorithm's training data.…”
Section: What Is a Bias?mentioning
confidence: 99%
“…A study on mammography screening, for example, has shown that radiologists were less likely to detect malignant breast lesions in patients with a minority ethnic background or low income [19]. The higher rate of false negatives in these patients suggests that health inequities are not only due to these groups' diminished access to services but are also influenced by radiologists' stereotypes and prejudices [12].…”
Section: What Biases Are Inequitable?mentioning
confidence: 99%
“…More importantly, patients being cared for in clinical departments where knowledge of disparities or cultural competency training is lacking may experience greater disparities themselves. For those involved in training technologists, medical students, or residents, there are resources available to give them a basic introduction to health care disparities and the delivery of culturally competent care [27][28][29][30][31][32]. Fostering education in these areas is a prerequisite to a professional community well equipped to discuss and deal with health care disparities.…”
Section: What Can I Do?mentioning
confidence: 99%